Pengaruh Modal Intelektual Pada Kinerja Organisasional: Sebuah Pendekatan Komplementarian - Hamdi Harmen; - Fairuzzabadi; - Farid (Conference In Business, Accounting, And Management (CBAM), 2012)
The study aims to examine the effect of intellectual capital’s components – human, structural, and relational capital, and their interactions on the organizational performance in a sample of private higher education in Yogyakarta. The regressions results indicated organizational performance in the dimension of organizational effectiveness can be well-explained by each component of intellectual capital. The results also indicated the interactions among human capital and relational capital had a synergistic or enhancing interactions in explaining performance of higher education institution.Keywords: intellectual capital, organizational performance, higher education institution.